La caña de azúcar en el Perú y el proceso de globalización - Barrientos Felipa, Pedro (2009)
The international community is finding new fuels that have as main feature the low cost and renewable. Ethanol is a fuel that has these characteristics and used for production of agricultural inputs. One of these agricultural inputs is the sugar cane, agricultural product in which Peru has experience, but as an input of sugar. Other technology is required. This is an opportunity that can be exploited as a country, even surpassing the possibilities of investors. There is an international market to satisfy, because the current producers do not yet achieved, but we must not forget that you are in the market for commodities. The article discusses the process of globalization leads to the logical path and should be exploited by those countries that are able to do so.